THE DIAGNOSTICS OF PERSONALITY TOLERANCE OF FOREIGN LANGUAGE TEACHERS - Demisenova, Sh.S.; Kharlamova, A.V. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
The diagnostics allows to track the dynamics of the development of personality tolerance of foreign language teachers. The most effective diagnostic tools for fixing the level of personality tolerance of foreign language teachers are considered. To solve the problem of complex diagnostics of individual tolerance, the diagnostic scheme of the study of ethnic tolerance by A.G. Asmolov, E.I. Shlyagina can be used. This article is of on the overview nature.
Keywords: tolerance; foreign language teachers; diagnostics; methods of tolerance diagnosis; diagnostic scheme